Relative share, frequency and correlation of restorations in both dental dentitions in childhood - Dobrinka Mitkova Damyanova; Radosveta Andreeva-Borisova (Intelektual Pustaka Media Utama, 2021)
This research aimed to analyze of the relative share, frequency and correlation of restorations in both dental dentitions in childhood. The decayed, missing, and filled permanent teeth (DMFT) index is one of the most commonly used indices in epidemiologic surveys of dental caries. It quantifies dental health status based on the number of carious, missing and filled teeth. A total of 602 schoolchildren in Varna, aged 3-18 years were selected for this study. The children have a determined high caries risk DMFT index >1. The patients are divided into 16 groups according to age limit. The research takes place in the Faculty of Dental Medicine, Medical University of Varna, in the time period 2016-2018. This study is retrospective, based on medical data of the participants. Pearson's correlation and simple linear regression were used to estimate the correlation between restorations, DMF (T+t) and age. The average value of determining the level of caries of the examined groups of children is DMF (T+t) =5.46±3.95 (range 0-20). With the correlation analysis we proved a direct dependence of the ratio. The number of preventive fillings with photopolymers and composites increased with increasing age of the studied children (r=0.725; p<0.001). Their high distribution among the studied patients was established by determining the average frequency of carious lesions. The correlation analysis determined that with increasing age of the patients the number and frequency of composite restorations and sealants in the control groups increased.